A inferência no livro didático: análise de atividades de compreensão e interpretação textual - LÔBO, Célia Márcia Gonçalves Nunes (2012)
This research is based on studies of Textual Linguistics and argues that the ability of making inference is part of the process of reading and comprehension process, because it is through the inference that the reader constructs new knowledge from the combination of existing data and facts in his/her memory. When considering that the textbook is a tool used by teachers in the classroom, this work had as main objective, to investigate how the authors of the textbook approach to work with the inferential ability in the collection of books most frequently adopted in Municipal Schools in Goiânia-GO, Brazil, from 6th to 9th grade in elementary school, Portuguese: language, by the authors Cereja and Magalhães (2009). This research was characterized with a mixed methodological approach, since it was performed a document and qualitative analysis and, simultaneously, quantitative data were also used. In view of the purpose of this study, the issues of understanding and interpretation of the texts in this collection were taken as object of investigation. To define the corpus, 779 questions of textual interpretation and understanding were analyzed. Data analysis was developed based on the inferential categories proposed by Marcuschi (2008) and Vidal-Abarca and Rico (2003), as well as the types of questions developed by Marcuschi (2008), which allowed categorizing the questions of textual study of the collection. Grounded methodological assumptions concerning the evidentiary paradigm, it was possible to find a work with the inferential ability in the collection and discuss some special data revealed in the investigation of natural corpus. The analysis showed that the textbook has provided the work of the inferential ability through verbal and nonverbal texts, and that the study of verbal texts provides more questions about inferential than nonverbal texts. An overview of the collection, adding to activities related to verbal and nonverbal texts, showed that there are more inferential questions that require a reading lying on the horizon of highest understanding than in questions of superficial order.